Sign Languages of the World: A Comparative Handbook - Bakken Jepsen, Julie; Lutalo-Kiingi, Sam; McGregor, William B.; De Clerck, Goedele (De Gruyter, 2015)
Sign Language; Deaf history; Deaf Education; Linguistic Typology